The Urgency of Implementing Conjugal Visit for Inmates from the Perspective of Positive Law and Human Rights - Hikmah, Faidatul; Hakim, Nurul Adillah; Roka, Tarisma Adha; Yokotani, Yokotani (Universitas Semarang, 2024)
This study examines the urgency of implementing conjugal visits in Indonesia through the lens of positive law and human rights, with a case study at the Class IIA Correctional Institution in Pangkalpinang. Limited access to healthy sexual relations with spouses contributes to stress, behavioral problems, and the spread of infectious diseases in overcrowded facilities. Conjugal visits are proposed to improve inmates' psychological well-being, maintain family ties, and support rehabilitation efforts. The research employs interviews, field observations, and literature reviews to address five key objectives: (1) identifying the legal vacuum in existing regulations, (2) examining practices related to inmates' sexual needs, (3) analyzing the relationship between overcrowding and deviant sexual behavior, (4) exploring legal considerations necessary for implementing conjugal visits, and (5) identifying challenges and proposing practical solutions. The findings show that conjugal visits reduce deviant sexual behavior, lower infection risks, and strengthen family relationships, thereby aiding successful reintegration into society. However, obstacles include the absence of a clear legal framework, budget constraints, and inadequate facilities in correctional institutions. This study emphasizes the need for legal reform, recommending a phased implementation of conjugal visits based on international best practices. Its novelty lies in proposing a progressive policy that aligns with the right to family life and procreation, as guaranteed by Articles 28B and 28H of the 1945 Constitution and the 1957 Standard Minimum Rules for the Treatment of Prisoners.